AISAS ANALYSIS OF KOREAN CELEBRITY IN INDONESIAN PRODUCT ADVERTISEMENT - Pratiwi, Indah Pratiwi (Departemen Ilmu Komunikasi, Fakultas Ilmu Soal dan Ilmu Politik. Universitas Pejuang Republik Indonesia, 2022)
In recent years K-Pop has massively penetrated Indonesian advertising. Multiple Indonesian companies has been started to hire Korean actors as their Brand Ambassadors (BA) for their products. The fascinating part about this phenomenon is that the products they advertised are mostly local products and those are not sold outside Indonesia. Meanwhile, numbers of research have proved that Word of Mouth happened due to previous users, especially around their circle, have had same experiences with the same products or services, hence they will recommend the products. However, if local products are promoted by foreigners, there are particular aspects will also affect consumer behaviour. The purpose of the study was to determine consumer behaviour when viewing local product advertisement starred by these Korean celebrities using the AISAS model. The research method used is qualitative with